Sodobna uporaba zdravilnih rastlin v Evropski uniji - Janeš, Damjan (Farmacevtski vestnik, 2013)
Popularity and use of medicinal herbs rises rapidly in the world and this trend is also followed by European Union (EU). The use of regulated herbal medicinal products ensures quality, safety and efficacy due to strict control protocols in EU, but this does not apply to food supplements. The use of unregulated and illegally distributed herbal products, which became easy accessible by rapidly developing internet services, can be a serious threat to health. There is also a problem of patients' attitude toward medicinal herbs. Since herbal medicines are of natural origin, patients are convinced, they are safe and without any adverse effects; therefore they frequently don't follow recommended dosage and duration of the treatment. Great popularity of medicinal herbs also stimulates the patients to collect plants from the natural environment which can damage fragile ecosystems. On the other hand frequent lack of adequate botanical knowledge results in confusion with toxic plants, sometimes with fatal consequences. In the era of modern information society, being under pressure of advertising, patients must be adequately informed to ensure they use herbal medicinal products of high quality, safety and efficacy. In this process a professional advice from a pharmacist is extremely important.
Keywords: European Union; Evropska unija; uporaba; zdravila rastlinskega izvora; zdravilne rastline